2019
DOI: 10.32795/widyakesehatan.v1i2.461
|View full text |Cite
|
Sign up to set email alerts
|

Meditasi Untuk Mengatasi Kecemasan Pada Ibu Hamil

Abstract: Seorang ibu pada masa kehamilan akan mengalami perubahan-perubahan baik fisik maupun psikologi seperti kecemasan. Upaya tradisional komplementer yang dilakukan dalam mengatasi kecemasan pada ibu hamil yaitu dengan meditasi. Meditasi yaitu metode memusatkan pikiran yang dapa membantu ibu berpikir positif dan memberikan rasa tenang dan bahagia. Tujuan penelitian ini untuk mengetahui meditasi, tata laksana meditasi dan implikasi meditasi kepada ibu hamil. Jenis penelitian ini kualitatif menggunakan metode snow ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
3
0
5
Order By: Relevance
“…This is closely related to the effect of psychological calm of mothers who receive meditation and positive affirmation exercises that have an impact on the labor duration and the APGAR scores of newborns. It is in line with the results of a study carried out by Suristyawati et al, (2019) showing that meditation is able to overcome anxiety in pregnant women. The presence of calm and comfort in pregnant women has an effect on the ability of the placenta to supply oxygen to the fetus.…”
Section: The Effect Of Meditation and Positive Affirmations On Apgar ...supporting
confidence: 90%
See 3 more Smart Citations
“…This is closely related to the effect of psychological calm of mothers who receive meditation and positive affirmation exercises that have an impact on the labor duration and the APGAR scores of newborns. It is in line with the results of a study carried out by Suristyawati et al, (2019) showing that meditation is able to overcome anxiety in pregnant women. The presence of calm and comfort in pregnant women has an effect on the ability of the placenta to supply oxygen to the fetus.…”
Section: The Effect Of Meditation and Positive Affirmations On Apgar ...supporting
confidence: 90%
“…It is also in line with a study conducted by Kartikasari et al (2020) reported that meditation using prenatal yoga techniques had a significant effect on increasing levels of endorphins, shorter labor times and stronger uterine contractions than those who did not receive yoga/meditation practice during pregnancy. The implications after meditation for pregnant women can form serotonin and endorphins hormones, which have an effect on decreasing anxiety levels and blood pressure and resulting in relaxation of all muscle, nerve and mind functions (Suristyawati et al, 2019). Cholifah et al (2017) stated that positive affirmations are effective in providing psychological changes to pregnant women with pre-eclampsia cases.…”
Section: The Effect Of Meditation and Positive Affirmations On The La...mentioning
confidence: 99%
See 2 more Smart Citations
“…Seorang ibu selama proses kehamilannya akan mengalami berbagai perubahan, baik perubahan fisiologis maupun psikologis. Adanya perubahan tersebut disebabkan karena adanya peningkatan hormon yaitu hormon estrogen dan progesterone, sehingga mengakibatkan aspek-aspek psikologis dan timbullah berbagai masalah pada ibu hamil yaitu kecemasan (Suristyawati,dkk, 2019).…”
Section: Pendahuluanunclassified